The Savannah with Royal palms and view of Government House, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
The postcard shows the stately palms in the Queen's Park Savannah, Port of Spain, Trinidad. In the distance, one of the country's historical landmarks, Government House, can be seen.
Colour: Black and white; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Parks--Trinidad and Tobago; Savannas--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Government House; Trees--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)